Patriotism is the Spiritual Basis of New Uzbekistan - Mirzadavlatovich, Yusupov Yodgormirza (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the theoretical aspects of issues related to the further development of patriotic education, the content and essence of the ongoing reforms to bring up the younger generation as patriotic harmoniously developed people.